Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-07T18:45:02+01:00
-6(x+1)=24
-6x-6=24/+6
-6x=30/ :(-6)
x=-5

-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5
2010-02-07T18:47:27+01:00
-6(x+1)=24
-6x -6=24
-6x=30 /*(-6)
x=-5

-7(x-2)=3x-1
-7x +14= 3x-1
-7x-3x=-1-14
-10x=-15 /÷(-10)
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 / ÷(-2)
x=-5
2010-02-07T18:48:29+01:00
-6(x+1)=24
-6x-6=24 |+6
-6x=30 | :(-6)
x=(-5)

-7(x-2)=3x-1
-7x+14=3x-1|-14
-7x=3x-15 |-3x
-10x=-15 | :(-10)
x=1,5

4(x-1)=6(1+x)
4x-4=6+6x |+4
4x=10+6x |-6x
-2x=10 |:(-2)
x=(-5)